Impact of Online Learning in the Era Pandemic Using the Algorithm C 4.5 - Windania Purba; Desty Rukmana; Derry Rosanta Br.sitanggang; Lina Sari Harefa (Information Technology and Science (ITScience), 2021)
The presence of the Corona virus disease 2019 (Covid-19) pandemic has changed the order in all corners of the world in a very short time. This large-scale change has occurred in the last two years starting from 2019 until now. This has resulted in the world of education experiencing major changes in the teaching and learning process. The learning process during the COVID-19 pandemic (online) is very much different from the previous learning process (face to face). This is a big problem in the world of education. The online learning policy, which was thought to be the solution to this problem, turned out to be just a bridge to break the passion for learning for students. evidenced by the impact felt by students during online learning. The satisfaction of online learning by Prima Indonesia University students can be seen from the results of the keosener (google form) that the researcher has distributed to 501 students. Researchers use data mining to explore important information that is expected to be used as consideration for enforcing the current online learning process. Researchers use the C 4.5 Algorithm method in data mining in order to bring out the impact of online learning. Measurement of satisfaction level is done by calculating the Entropy and Gain of each data that becomes a Decision tree and testing the results using Rapid Miner. The C 4.5 algorithm is very helpful for researchers to find out the impact of online learning carried out during the covid 19 pandemic. From the results of calculations and testing, it shows that there is a decrease in student interest in learning in the online learning process. this concludes that online learning in the pandemic era has a negative impact on students at Prima Indonesia University.